A low carbon magnesium carbon brick and its preparation method

By crushing, wet grinding and layering of post-magnesium carbon bricks, combined with heat treatment and temperature-raising oxygen treatment, low-carbon magnesium carbon bricks with low porosity and good refractory properties were prepared, which solved the problems of high porosity and difficult to control the amount of carbon introduced by recycled magnesium carbon bricks, and achieved efficient reuse of post-magnesium carbon bricks.

CN119390428BActive Publication Date: 2025-04-25HONGXIANG ZHONGKE (LIAONING) REFRACTORY CO LTD +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510002307.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-01-02
Publication Date
2025-04-25
Estimated Expiration
2045-01-02

AI Technical Summary

Technical Problem

The existing recycled magnesium carbon bricks have high porosity and are difficult to control the amount of carbon introduced, which affects its fire resistance and service life.

Method used

Low-carbon magnesium carbon bricks are prepared by crushing, wet grinding, sieve and mixing them with electromelted magnesium sand, graphite, phenolic resin binder and other materials, and layering process of magnesium carbon sand with different particle sizes is adopted, combined with drying gun heat treatment and heating oxygen-raising treatment to prepare low-carbon magnesium carbon bricks.

Benefits of technology

The porosity of the magnesium carbon bricks is reduced to ≤1.6%, the pressure resistance strength of the room temperature is ≥75.5Mpa, and the flexural strength of 1250℃×0.5h is ≥14.9Mpa, which realizes the effective reuse of magnesium carbon bricks after use and reduces production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119390428B_ABST
    Figure CN119390428B_ABST
Patent Text Reader

Abstract

The present application relates to the technical field of magnesium carbon bricks, and specifically discloses a low-carbon magnesium carbon brick and a preparation method thereof. A low-carbon magnesium carbon brick is made of the following raw materials by mass: 65-75 parts of fused magnesia sand, 20-24 parts of waste magnesium carbon sand, 3-5 parts of graphite, and 5-7 parts of phenolic resin adhesive; the used magnesium carbon brick is crushed to obtain raw sand A, raw sand B and raw sand C with different particle size distributions, and the raw sand is processed to prepare the first particle size magnesium carbon sand, the second particle size magnesium carbon sand and the third particle size magnesium carbon sand, and the waste magnesium carbon sand of each particle size is mixed to obtain waste magnesium carbon sand; the fused magnesia sand, the waste magnesium carbon sand, the graphite and the phenolic resin adhesive are stirred and mixed, and then transferred to the mold for pressurized pressing and molding, heat treated with a drying gun, and baked to obtain a low-carbon magnesium carbon brick. The low-carbon magnesium carbon brick made using the waste magnesium carbon sand of the present application has a lower apparent porosity, and can reduce the amount of carbon introduced, so as to realize the reuse of the used magnesium carbon brick.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of magnesia carbon bricks, and more specifically, to a low-carbon magnesia carbon brick and a preparation method thereof. Background Art

[0002] Magnesia carbon brick is a composite refractory material made of high melting point alkaline magnesium oxide and carbon material as raw materials, with various non-oxide additives added and prepared by high pressure pressing and other methods. It has excellent refractory properties and thermal conductivity.

[0003] Magnesium carbon bricks play an important role in high-temperature industrial fields such as high-temperature furnaces and steel smelting, but the waste problem is also particularly serious. In the process of steel metallurgical industry, magnesium carbon bricks with a small amount of loss are often discarded as a whole because of the risk of affecting the quality of molten steel, which greatly increases the waste of magnesium carbon brick raw materials. In addition, the raw materials of magnesium carbon bricks themselves are difficult to regenerate. If the used magnesium carbon bricks are not reused, the cost of industrial production will increase. Therefore, more and more companies have begun to study the reuse process of used magnesium carbon bricks and have made certain progress.

[0004] At present, the recycling of industrial magnesia carbon bricks usually takes spent magnesia carbon bricks as recycled raw materials, mixes them with fused magnesia sand rich in magnesium oxide, adds a binder and presses them for heat preservation to obtain recycled magnesia carbon bricks, but this preparation process also has defects. Since spent magnesia carbon bricks are affected by decarburization and slag invasion, there are many pores and defects in their structure. If they are directly blended with fused magnesia sand, the apparent porosity of the produced recycled magnesia carbon bricks will increase. This structure is not conducive to the refractory properties of recycled magnesia carbon bricks. The increase in apparent porosity increases the risk of recycled magnesia carbon bricks being invaded by slag during use and aggravates the consumption rate of magnesia carbon bricks. Therefore, in the preparation process of recycled magnesia carbon bricks, it is also necessary to optimize raw materials and processes to reduce the risk of increased apparent porosity.

[0005] A Chinese patent document with the publication number CN117658605B discloses an aluminum-magnesium-carbon brick and a preparation method thereof. In the document, a graphene oxide modified with 4-aminobenzyl diethyl phosphate is added to the raw material components of the magnesium-carbon brick, and the modified graphene oxide can reduce the apparent porosity of the aluminum-magnesium-carbon brick product.

[0006] Although the modified graphene oxide used in the above document can reduce the apparent porosity of magnesium carbon brick products, the addition of graphene oxide increases the carbon content in the product and cannot effectively control carbon. Therefore, there is still a need to find a method to reduce the apparent porosity and carbon introduction amount of recycled magnesium carbon bricks. Summary of the invention

[0007] In order to further reduce the apparent porosity of the recycled magnesia carbon brick and reduce the amount of carbon introduced, the present application provides a low-carbon magnesia carbon brick and a preparation method thereof.

[0008] In a first aspect, the present application provides a low-carbon magnesia carbon brick, which is made of the following raw materials in parts by weight: 65-75 parts of fused magnesia sand, 20-24 parts of waste magnesia carbon sand, 3-5 parts of graphite, and 5-7 parts of phenolic resin adhesive;

[0009] The waste magnesia carbon sand is prepared by the following steps:

[0010] (1) crushing, wet-grinding and sieving the used magnesia carbon bricks, and screening according to the particle size to obtain raw sand A, raw sand B and raw sand C; the particle size of the raw sand A is 2-2.5 mm, the particle size of the raw sand B is 0.5-1 mm, and the particle size of the raw sand C is ≤0.05 mm;

[0011] (2) mixing raw sand A with a silica-based sol liquid to obtain a mixed mortar, and then drying and crushing the mixed mortar to obtain magnesium carbon sand of a first particle size;

[0012] (3) mixing tin powder, indium powder and raw sand B, wet grinding to obtain a mixed slurry, adding a binder, stirring, drying under anaerobic conditions, and crushing to obtain mixed sand particles, and screening the mixed sand particles with a particle size in the range of 1-2 mm as the second particle size magnesium carbon sand;

[0013] (4) heating the raw sand C and subjecting it to oxygen treatment, and cooling it to obtain magnesium carbon sand of the third particle size;

[0014] (5) Mix the first-size magnesia carbon sand, the second-size magnesia carbon sand and the third-size magnesia carbon sand.

[0015] By adopting the above technical scheme, three kinds of differently treated magnesia carbon sand can be obtained. Due to the difference in the particle size of each magnesia carbon sand, a stratification effect will be produced during the mixing and molding process. Among them, the first magnesia carbon sand is concentrated in the upper layer of the low-carbon magnesia carbon brick. After subsequent heat treatment with a drying gun, the solidified silicon-based sol liquid attached to the surface is transformed into silicon dioxide microcrystals, which can be used to resist the invasion of slag into the interior of the magnesia carbon brick; the second magnesia carbon sand is concentrated in the middle layer of the low-carbon magnesia carbon brick. During use, the metal tin and indium mixed therein will be converted into a low-melting-point tin-indium binary alloy liquid, and the volume will expand, which can be used to fill the pores between the adjacent waste magnesia carbon sand and other components; the third magnesia carbon sand is concentrated in the bottom layer of the low-carbon magnesia carbon brick. After heating and oxygen treatment, the carbon reduction effect can be achieved. Carbon itself is an excellent thermal conductor. By reducing carbon, the heat loss of the furnace body during use can be reduced, thereby obtaining a low-carbon insulation layer surrounded by the third magnesia carbon sand in the furnace.

[0016] Preferably, the average particle size of the fused magnesia is 1.5 mm.

[0017] By adopting the above technical solution, the stratification effect of the waste magnesia carbon sand can be ensured by using the fused magnesia carbon sand with the particle size distribution.

[0018] Preferably, in step (2), the silicon-based sol solution is prepared from water, tetraethyl orthosilicate, γ-glycidyloxypropyltrimethoxysilane, 0.1 mol / L hydrochloric acid, polyvinyl pyrrolidone, and N,N,N-trimethyl chitosan in a mass volume ratio of (30-35) g: (3-3.5) g: 1 g: (1-2.5) mL: 0.15 g: (0.2-0.3) g.

[0019] By adopting the above technical solution, the prepared silicon-based sol liquid can maintain a relatively low viscosity, avoiding stickiness and the formation of large silicon dioxide clusters after subsequent heat treatment with a drying gun, which reduces the use effect. In the silicon-based sol liquid, ethyl orthosilicate and γ-glycidyloxypropyltrimethoxysilane are hydrolyzed in an acidic aqueous solvent to form a silicon-based cross-linked network structure, which can be mixed with raw sand A to wrap raw sand A. The viscosity of the silicon-based sol liquid directly affects its wrapping effect on raw sand A.

[0020] Preferably, the raw sand A and the silica-based sol liquid are mixed in a mass ratio of (2-3):1;

[0021] The average particle size of the tin powder is 75 microns, and the average particle size of the indium powder is 50 microns;

[0022] The binder is bentonite.

[0023] Preferably, in step (2), the particle size of the first-size magnesia carbon sand is 2.5-3 mm.

[0024] By adopting the above technical solution, the first-size magnesia-carbon sand can be concentratedly distributed in the upper layer of the low-carbon magnesia-carbon bricks after mixing and molding.

[0025] Preferably, in step (3), the mass ratio of tin powder, indium powder and raw sand B is (5-7): (1-1.5): (50-75).

[0026] By adopting the above technical solution, the best combination effect of raw materials can be obtained.

[0027] Preferably, in step (4), the temperature-raising and oxygen-passing treatment includes a first stage of temperature-raising, oxygen-passing, and a second stage of temperature-raising, and the operation is as follows:

[0028] Stage 1 heating: heating to 500-600℃ at a rate of 5-7℃ / min;

[0029] Oxygen flow: oxygen was introduced at a rate of 20 mL / min, and then stopped after 10 min;

[0030] Second stage heating: heating to 745-825℃ at a rate of 10-15℃ / min.

[0031] By adopting the above technical solution, the carbon content in the raw sand C can be effectively reduced. The introduction of oxygen during the staged heating and between the first and second heating stages can ensure that the graphite is gradually decomposed or volatilized at the continuously increasing temperature, thereby more effectively removing the carbon in the raw sand C and improving the quality of the third-size magnesium carbon sand obtained after the treatment.

[0032] Preferably, in step (5), the first-size magnesia-carbon sand, the second-size magnesia-carbon sand and the third-size magnesia-carbon sand are mixed in a mass ratio of 1:2:1.

[0033] By adopting the above technical solution, the combination of magnesia carbon sands of various particle sizes for obtaining low-carbon magnesia carbon bricks has the best effect.

[0034] In a second aspect, the present application provides a method for preparing a low-carbon magnesium-carbon brick, comprising the following steps:

[0035] The fused magnesia sand, waste magnesia carbon sand, graphite and phenolic resin binder are stirred and mixed, and then transferred to a mold for pressure pressing and molding, and heat treated with a drying gun, and then baked to obtain low-carbon magnesia carbon bricks.

[0036] Preferably, the pressurized compression molding is performed at a pressure of 135-175 MPa.

[0037] By adopting the above technical solution, the obtained low-carbon magnesium carbon brick has the best compression and buckling resistance effect.

[0038] Preferably, the temperature of the heat treatment with the drying gun is 550-650° C., and the treatment time is 3-5 seconds.

[0039] By adopting the above technical solution, the heat treatment effect of low-carbon magnesia-carbon bricks is best.

[0040] Preferably, the baking is carried out at 150-250° C. for 12-15 hours.

[0041] By adopting the above technical solution, the obtained low-carbon magnesia-carbon bricks can achieve the best use effect.

[0042] In summary, this application has the following beneficial effects:

[0043] 1. This application adopts different processing techniques to obtain three kinds of magnesia carbon sand of different particle sizes, which are respectively concentrated in the upper, middle and lower layers of low-carbon magnesia carbon bricks after mixing and forming. Among them, the first-size magnesia carbon sand is concentrated in the upper layer of low-carbon magnesia carbon bricks. After subsequent heat treatment with a drying gun, the solidified silicon-based sol liquid attached to the surface is transformed into silicon dioxide microcrystals, which can be used to resist the invasion of slag into the interior of the magnesia carbon bricks; the second-size magnesia carbon sand is concentrated in the middle layer of low-carbon magnesia carbon bricks. During use, the metal tin and indium mixed therein will be converted into a low-melting-point tin-indium binary alloy liquid, and the volume will expand, which can be used to fill the pores between the adjacent magnesia carbon sand and other components; the third-size magnesia carbon sand is concentrated in the bottom layer of low-carbon magnesia carbon bricks. After heating and oxygen treatment, it can achieve a carbon reduction effect, reduce heat loss during the use of the furnace body, and obtain a low-carbon insulation layer surrounded by the third-size magnesia carbon sand in the furnace.

[0044] 2. The low-carbon magnesia-carbon bricks made from the waste magnesia-carbon sand of this application have an apparent porosity of ≤1.6%, a compressive strength at room temperature of ≥75.5Mpa, and a high-temperature flexural strength of 1250℃×0.5h of ≥14.9Mpa.

[0045] 3. The low-carbon magnesia-carbon bricks made from the waste magnesia-carbon sand of the present application have easy-to-obtain raw materials, and can realize the reuse of the used magnesia-carbon bricks, saving production costs and facilitating large-scale industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0046] Figure 1 The apparent porosity and bulk density of the low carbon magnesia carbon bricks of Examples 1-5 and Comparative Examples 1-2 of the present application. DETAILED DESCRIPTION

[0047] Example 1

[0048] In this embodiment, the magnesia carbon brick is made of the following raw materials by weight: 650g of fused magnesia sand (average particle size 1.5mm), 200g of waste magnesia carbon sand, 30g of graphite, 50g of phenolic resin adhesive, 6g of aluminum powder, and 2.5g of silicon powder.

[0049] Take 250g of used magnesia carbon bricks and use a 400mmX600mm jaw crusher for preliminary crushing, with a power of 5KW, and process for 20 minutes. Then transfer the preliminary crushed material to a ball mill, use deionized water as the ball milling medium, control the ball milling speed to 135rpm, and wet grind with a ball-to-material ratio of 2:1, and then dry to obtain raw sand. Filter the raw sand with a sieve and divide it according to the particle size distribution: the raw sand with a particle size of 2-2.5mm is recorded as raw sand A, the raw sand with a particle size of 0.5-1mm is recorded as raw sand B, and the raw sand with a particle size ≤0.05mm is recorded as raw sand C.

[0050] Mix 50g of raw sand A with 25g of silica-based sol liquid, adjust the magnetic stirring speed to 150rpm, mix for 20min to obtain a mixed mortar, dry the mixed mortar at 40°C for 5h, and then crush to obtain composite sand particles, and screen the composite sand particles with a particle size in the range of 2.5-3mm as the first particle size magnesia carbon sand.

[0051] 10g of tin powder (average particle size of 75 microns), 2g of indium powder (average particle size of 50 microns) and 100g of raw sand B were mixed and put into a ball mill for non-abrasive wet grinding. Anhydrous ethanol was used as the ball milling medium, and the ball milling speed was controlled to 120rpm for 3 hours to obtain a mixed slurry. 2g of bentonite was added to the slurry, stirred and mixed evenly, and then dried at 90°C under oxygen isolation, and then re-crushed to obtain mixed sand particles, and the mixed sand particles with a particle size range of 1-1.5mm were screened as the second particle size magnesium carbon sand.

[0052] 50g of raw sand C was placed in a high-temperature reactor, and the temperature was raised to 500℃ at a rate of 5℃ / min, and then oxygen was introduced at a rate of 20mL / min. After 10min, the introduction of oxygen was stopped, and then the temperature in the high-temperature reactor was raised to 745℃ at a rate of 10℃ / min, and the temperature was kept constant for 1h, and then the heating was stopped. The temperature was naturally cooled to room temperature, the gas in the high-temperature reactor was emptied, and the residual solid powder was taken out to obtain the third-size magnesium carbon sand.

[0053] Mix 50 g of first-size magnesia-carbon sand, 100 g of second-size magnesia-carbon sand, and 50 g of third-size magnesia-carbon sand to obtain waste magnesia-carbon sand.

[0054] The steps for preparing magnesia carbon bricks in this embodiment are as follows:

[0055] Fused magnesia sand, graphite, aluminum powder, silicon powder, phenolic resin binder and waste magnesia carbon sand were added to the mixer and mixed for 0.5 hours. The mixture was then transferred to a mold and pressed at 135 MPa to obtain a shaped magnesia carbon brick. The surface of the shaped magnesia carbon brick was then treated with a drying gun at 550°C for 3 seconds, and then transferred to a drying furnace at 150°C for 12 hours to obtain a low-carbon magnesia carbon brick.

[0056] Among them, the chemical composition of fused magnesia (%wt) is: MgO 95.72%, CaO 2.15%, Fe 2 O 3 0.76%, SiO 2 0.34%. The chemical composition of waste magnesia carbon sand (%wt) is: MgO 79.23%, C 5.36%, CaO 6.27%, Fe 2 O 3 4.33%, SiO 21.80%. Phenolic resin adhesive (model: PF918, moisture ≤1%wt) was provided by Hebei Zetian Chemical Co., Ltd. The silicon-based sol solution was prepared by deionized water: ethyl orthosilicate: γ-glycidyloxypropyl trimethoxysilane: 0.1mol / L hydrochloric acid: polyvinyl pyrrolidone: N,N,N-trimethyl chitosan according to the mass volume ratio of 30g:3g:1g:1mL:0.15g:0.2g.

[0057] Example 2

[0058] In this embodiment, the magnesia carbon brick is made of the following raw materials by weight: 685g of fused magnesia sand (average particle size 1.5mm), 220g of waste magnesia carbon sand, 30g of graphite, 55g of phenolic resin adhesive, 5g of aluminum powder, and 3.5g of silicon powder.

[0059] Take 280g of used magnesia carbon bricks and use a 400mmX600mm jaw crusher for preliminary crushing, with a power of 5KW, and process for 25 minutes. Then transfer the preliminary crushed material to a ball mill, use deionized water as the ball milling medium, control the ball milling speed to 140rpm, and wet grind with a ball-to-material ratio of 2.5:1, and then dry to obtain raw sand. Filter the raw sand with a sieve and divide it according to the particle size distribution: the raw sand with a particle size of 2-2.5mm is recorded as raw sand A, the raw sand with a particle size of 0.5-1mm is recorded as raw sand B, and the raw sand with a particle size ≤0.05mm is recorded as raw sand C.

[0060] Mix 60g of raw sand A with 30g of silica-based sol liquid, adjust the magnetic stirring speed to 175rpm, mix for 20min to obtain a mixed mortar, dry the mixed mortar at 45°C for 5h, and then crush to obtain composite sand particles, and screen the composite sand particles with a particle size in the range of 2.5-3mm as the first particle size magnesia carbon sand.

[0061] 12g of tin powder (average particle size of 75 microns), 3g of indium powder (average particle size of 50 microns) and 120g of raw sand B were mixed and put into a ball mill for non-abrasive wet grinding. Anhydrous ethanol was used as the ball milling medium, and the ball milling speed was controlled to 125rpm for 3 hours to obtain a mixed slurry. 3.5g of bentonite was added to the slurry, stirred and mixed evenly, and then dried at 100°C under oxygen isolation conditions, and then re-crushed to obtain mixed sand particles, and the mixed sand particles with a particle size range of 1-1.5mm were screened as the second particle size magnesium carbon sand.

[0062] 60g of raw sand C was placed in a high-temperature reactor, and the temperature was raised to 550℃ at a rate of 7℃ / min. After that, oxygen was introduced at a rate of 20mL / min. After 10min, the introduction of oxygen was stopped. Then, the temperature in the high-temperature reactor was raised to 785℃ at a rate of 12℃ / min, and the temperature was kept constant for 2h. Then, the heating was stopped. The temperature was naturally cooled to room temperature, the gas in the high-temperature reactor was vented, and the residual solid powder was taken out to obtain the third-size magnesium carbon sand.

[0063] 55 g of first-size magnesia-carbon sand, 110 g of second-size magnesia-carbon sand, and 55 g of third-size magnesia-carbon sand were mixed to obtain waste magnesia-carbon sand.

[0064] The steps for preparing magnesia carbon bricks in this embodiment are as follows:

[0065] Fused magnesia sand, graphite, aluminum powder, silicon powder, phenolic resin binder and waste magnesia carbon sand were added to the mixer and mixed for 0.5 hours. The mixture was then transferred to a mold and pressed at 150 MPa to obtain a shaped magnesia carbon brick. The surface of the shaped magnesia carbon brick was then treated with a drying gun at 565°C for 4 seconds, and then transferred to a drying furnace at 150°C for 15 hours to obtain a low-carbon magnesia carbon brick.

[0066] Among them, the chemical composition of fused magnesia (%wt) is: MgO 95.72%, CaO 2.15%, Fe 2 O 3 0.76%, SiO 2 0.34%. The chemical composition of waste magnesia carbon sand (%wt) is: MgO 79.23%, C 5.36%, CaO 6.27%, Fe 2 O 3 4.33%, SiO 2 1.80%. Phenolic resin adhesive (model: PF918, moisture ≤1%wt) was provided by Hebei Zetian Chemical Co., Ltd. The silicon-based sol solution was prepared from deionized water: ethyl orthosilicate: γ-glycidyloxypropyl trimethoxysilane: 0.1mol / L hydrochloric acid: polyvinyl pyrrolidone: N,N,N-trimethyl chitosan according to the mass volume ratio of 32g:3g:1g:1.75mL:0.15g:0.2g.

[0067] Example 3

[0068] In this embodiment, the magnesia carbon brick is made of the following raw materials by weight: 700g of fused magnesia sand (average particle size 1.5mm), 220g of waste magnesia carbon sand, 45g of graphite, 60g of phenolic resin adhesive, 6.5g of aluminum powder, and 2g of silicon powder.

[0069] Take 280g of used magnesia carbon bricks and use a 400mmX600mm jaw crusher for preliminary crushing, with a power of 5KW and a processing time of 25min. Then transfer the preliminary crushed material to a ball mill, use deionized water as the ball milling medium, control the ball milling speed to 145rpm, and wet grind with a ball-to-material ratio of 2.5:1, and then dry to obtain raw sand. Filter the raw sand with a sieve and divide it according to the particle size distribution: the raw sand with a particle size of 2-2.5mm is recorded as raw sand A, the raw sand with a particle size of 0.5-1mm is recorded as raw sand B, and the raw sand with a particle size ≤0.05mm is recorded as raw sand C.

[0070] Mix 65g of raw sand A with 35g of silica-based sol liquid, adjust the magnetic stirring speed to 175rpm, mix for 30min to obtain a mixed mortar, dry the mixed mortar at 45°C for 5h, and then crush to obtain composite sand particles, and screen the composite sand particles with a particle size in the range of 2.5-3mm as the first particle size magnesia carbon sand.

[0071] 14g of tin powder (average particle size of 75 microns), 3g of indium powder (average particle size of 50 microns) and 150g of raw sand B were mixed and put into a ball mill for non-abrasive wet grinding. Anhydrous ethanol was used as the ball milling medium, and the ball milling speed was controlled to 130rpm for 5 hours to obtain a mixed slurry. 3.5g of bentonite was added to the slurry, stirred and mixed evenly, and then dried at 105°C under oxygen isolation conditions, and then re-crushed to obtain mixed sand particles, and the mixed sand particles with a particle size range of 1-1.5mm were screened as the second particle size magnesium carbon sand.

[0072] 65g of raw sand C was placed in a high-temperature reactor, and the temperature was raised to 600℃ at a rate of 7℃ / min, and then oxygen was introduced at a rate of 20mL / min. After 10min, the introduction of oxygen was stopped, and then the temperature in the high-temperature reactor was raised to 800℃ at a rate of 15℃ / min, and the temperature was kept constant for 1h, and then the heating was stopped. The temperature was naturally cooled to room temperature, the gas in the high-temperature reactor was emptied, and the residual solid powder was taken out to obtain the third-size magnesium carbon sand.

[0073] 55 g of first-size magnesia-carbon sand, 110 g of second-size magnesia-carbon sand, and 55 g of third-size magnesia-carbon sand were mixed to obtain waste magnesia-carbon sand.

[0074] The steps for preparing magnesia carbon bricks in this embodiment are as follows:

[0075] Fused magnesia sand, graphite, aluminum powder, silicon powder, phenolic resin binder and waste magnesia carbon sand were added to the mixer and mixed for 1 hour. The mixture was then transferred to a mold and pressed at 155 MPa to obtain a shaped magnesia carbon brick. The surface of the shaped magnesia carbon brick was then treated with a drying gun at 600°C for 5s, and then transferred to a drying furnace at 250°C for 13 hours to obtain a low-carbon magnesia carbon brick.

[0076] Among them, the chemical composition of fused magnesia (%wt) is: MgO 95.72%, CaO 2.15%, Fe 2 O 3 0.76%, SiO 2 0.34%. The chemical composition of waste magnesia carbon sand (%wt) is: MgO 79.23%, C 5.36%, CaO 6.27%, Fe 2 O 3 4.33%, SiO 21.80%. Phenolic resin adhesive (model: PF918, moisture ≤1%wt) was provided by Hebei Zetian Chemical Co., Ltd. The silicon-based sol solution was prepared by deionized water: ethyl orthosilicate: γ-glycidyloxypropyl trimethoxysilane: 0.1mol / L hydrochloric acid: polyvinyl pyrrolidone: N,N,N-trimethyl chitosan according to the mass volume ratio of 35g:3g:1g:1.5mL:0.15g:0.3g.

[0077] Example 4

[0078] In this embodiment, the magnesia carbon brick is made of the following raw materials by weight: 750g of fused magnesia sand (average particle size 1.5mm), 240g of waste magnesia carbon sand, 50g of graphite, 65g of phenolic resin adhesive, 7.5g of aluminum powder, and 1g of silicon powder.

[0079] Take 300g of used magnesia carbon bricks and use a 400mmX600mm jaw crusher for preliminary crushing, with a power of 5KW and a processing time of 25min. Then transfer the preliminary crushed material to a ball mill, use deionized water as the ball milling medium, control the ball milling speed to 155rpm, and wet grind with a ball-to-material ratio of 2.5:1, and then dry to obtain raw sand. Filter the raw sand with a sieve and divide it according to the particle size distribution: the raw sand with a particle size of 2-2.5mm is recorded as raw sand A, the raw sand with a particle size of 0.5-1mm is recorded as raw sand B, and the raw sand with a particle size ≤0.05mm is recorded as raw sand C.

[0080] Mix 75g of raw sand A with 25g of silica-based sol liquid, adjust the magnetic stirring speed to 175rpm, mix for 25min to obtain a mixed mortar, dry the mixed mortar at 45°C for 7h, and then crush to obtain composite sand particles, and screen the composite sand particles with a particle size in the range of 2.5-3mm as the first particle size magnesia carbon sand.

[0081] 13g of tin powder (average particle size of 75 microns), 1.8g of indium powder (average particle size of 50 microns) and 150g of raw sand B were mixed and put into a ball mill for non-abrasive wet grinding. Anhydrous ethanol was used as the ball milling medium, and the ball milling speed was controlled to 130rpm for 5 hours to obtain a mixed slurry. 3.5g of bentonite was added to the slurry, stirred and mixed evenly, and then dried at 100°C under oxygen isolation conditions, and then re-crushed to obtain mixed sand particles, and the mixed sand particles with a particle size range of 1-1.5mm were screened as the second particle size magnesium carbon sand.

[0082] 75g of raw sand C was placed in a high-temperature reactor, and the temperature was raised to 600℃ at a rate of 7℃ / min, and then oxygen was introduced at a rate of 20mL / min. After 10min, the introduction of oxygen was stopped, and then the temperature in the high-temperature reactor was raised to 825℃ at a rate of 15℃ / min, and the temperature was kept constant for 2h, and then the heating was stopped. The temperature was naturally cooled to room temperature, the gas in the high-temperature reactor was emptied, and the residual solid powder was taken out to obtain the third-size magnesium carbon sand.

[0083] 60 g of first-size magnesia-carbon sand, 120 g of second-size magnesia-carbon sand, and 60 g of third-size magnesia-carbon sand are mixed to obtain waste magnesia-carbon sand.

[0084] The steps for preparing magnesia carbon bricks in this embodiment are as follows:

[0085] Fused magnesia sand, graphite, aluminum powder, silicon powder, phenolic resin binder and waste magnesia carbon sand were added to the mixer and mixed for 1 hour. The mixture was then transferred to the mold and pressed under 175 MPa to obtain a shaped magnesia carbon brick. The surface of the shaped magnesia carbon brick was then treated with a drying gun at 645°C for 3s, and then transferred to a drying furnace at 250°C for 14 hours to obtain a low-carbon magnesia carbon brick.

[0086] Among them, the chemical composition of fused magnesia (%wt) is: MgO 95.72%, CaO 2.15%, Fe 2 O 3 0.76%, SiO 2 0.34%. The chemical composition of waste magnesia carbon sand (%wt) is: MgO 79.23%, C 5.36%, CaO 6.27%, Fe 2 O 3 4.33%, SiO 2 1.80%. Phenolic resin adhesive (model: PF918, moisture ≤1%wt) was provided by Hebei Zetian Chemical Co., Ltd. The silicon-based sol solution was prepared from deionized water: ethyl orthosilicate: γ-glycidyloxypropyl trimethoxysilane: 0.1mol / L hydrochloric acid: polyvinyl pyrrolidone: N,N,N-trimethyl chitosan according to the mass volume ratio of 35g:3.5g:1g:2.5mL:0.15g:0.3g.

[0087] Example 5

[0088] In this embodiment, the magnesia carbon brick is made of the following raw materials by weight: 750g of fused magnesia sand (average particle size 1.5mm), 240g of waste magnesia carbon sand, 50g of graphite, 70g of phenolic resin adhesive, 5.5g of aluminum powder, and 3g of silicon powder.

[0089] Take 300g of used magnesia carbon bricks and use a 400mmX600mm jaw crusher for preliminary crushing, with a power of 5KW, and process for 30 minutes. Then transfer the preliminary crushed material to a ball mill, use deionized water as the ball milling medium, control the ball milling speed to 155rpm, and wet grind with a ball-to-material ratio of 2.5:1, and then dry to obtain raw sand. Filter the raw sand with a sieve and divide it according to the particle size distribution: the raw sand with a particle size of 2-2.5mm is recorded as raw sand A, the raw sand with a particle size of 0.5-1mm is recorded as raw sand B, and the raw sand with a particle size ≤0.05mm is recorded as raw sand C.

[0090] Mix 75g of raw sand A with 25g of silica-based sol liquid, adjust the magnetic stirring speed to 175rpm, mix for 30min to obtain a mixed mortar, dry the mixed mortar at 50°C for 7h, and then crush to obtain composite sand particles, and screen the composite sand particles with a particle size in the range of 2.5-3mm as the first particle size magnesia carbon sand.

[0091] 14g of tin powder (average particle size of 75 microns), 3g of indium powder (average particle size of 50 microns) and 150g of raw sand B were mixed and put into a ball mill for non-abrasive wet grinding. Anhydrous ethanol was used as the ball milling medium, and the ball milling speed was controlled to 130rpm for 5 hours to obtain a mixed slurry. 3.5g of bentonite was added to the slurry, stirred and mixed evenly, and then dried at 105°C under oxygen isolation conditions, and then re-crushed to obtain mixed sand particles, and the mixed sand particles with a particle size range of 1-1.5mm were screened as the second particle size magnesium carbon sand.

[0092] 75g of raw sand C was placed in a high-temperature reactor, and the temperature was raised to 600℃ at a rate of 7℃ / min, and then oxygen was introduced at a rate of 20mL / min. After 10min, the introduction of oxygen was stopped, and then the temperature in the high-temperature reactor was raised to 825℃ at a rate of 15℃ / min, and the temperature was kept constant for 2h, and then the heating was stopped. The temperature was naturally cooled to room temperature, the gas in the high-temperature reactor was emptied, and the residual solid powder was taken out to obtain the third-size magnesium carbon sand.

[0093] 60 g of first-size magnesia-carbon sand, 120 g of second-size magnesia-carbon sand, and 60 g of third-size magnesia-carbon sand are mixed to obtain waste magnesia-carbon sand.

[0094] The steps for preparing magnesia carbon bricks in this embodiment are as follows:

[0095] Fused magnesia sand, graphite, aluminum powder, silicon powder, phenolic resin binder and waste magnesia carbon sand were added to the mixer and mixed for 1 hour. The mixture was then transferred to a mold and pressed at 175 MPa to obtain a shaped magnesia carbon brick. The surface of the shaped magnesia carbon brick was then treated with a drying gun at 650°C for 5 seconds, and then transferred to a drying furnace at 250°C for 15 hours to obtain a low-carbon magnesia carbon brick.

[0096] Among them, the chemical composition of fused magnesia (%wt) is: MgO 95.72%, CaO 2.15%, Fe 2 O 3 0.76%, SiO 2 0.34%. The chemical composition of waste magnesia carbon sand (%wt) is: MgO 79.23%, C 5.36%, CaO 6.27%, Fe 2 O 3 4.33%, SiO 2 1.80%. Phenolic resin adhesive (model: PF918, moisture ≤1%wt) was provided by Hebei Zetian Chemical Co., Ltd. The silicon-based sol solution was prepared from deionized water: ethyl orthosilicate: γ-glycidyloxypropyl trimethoxysilane: 0.1mol / L hydrochloric acid: polyvinyl pyrrolidone: N,N,N-trimethyl chitosan according to the mass volume ratio of 35g:3.5g:1g:2.5mL:0.15g:0.3g.

[0097] Comparative Example 1

[0098] The low-carbon magnesia carbon brick of this comparative example is made of the following raw materials by weight: 650g of fused magnesia sand (average particle size 1.5mm), 200g of waste magnesia carbon sand, 30g of graphite, 50g of phenolic resin adhesive, 6g of aluminum powder, and 2.5g of silicon powder.

[0099] Take 250g of used magnesia carbon bricks and use a 400mmX600mm jaw crusher for preliminary crushing, with a power of 5KW, and process for 20 minutes. Then transfer the preliminary crushed material to a ball mill, use deionized water as the ball milling medium, control the ball milling speed to 135rpm, and wet grind with a ball-to-material ratio of 2:1, and then dry to obtain raw sand. Filter the raw sand with a sieve and divide it according to the particle size distribution: the raw sand with a particle size of 2-2.5mm is recorded as raw sand A, the raw sand with a particle size of 0.5-1mm is recorded as raw sand B, and the raw sand with a particle size ≤0.05mm is recorded as raw sand C;

[0100] Mix 50g of raw sand A, 100g of raw sand B, and 50g of raw sand C to obtain waste magnesia carbon sand.

[0101] The preparation steps of the low carbon magnesia carbon bricks in this comparative example are the same as those in Example 1.

[0102] Comparative Example 2

[0103] The difference between this comparative example and Example 1 is that copper powder and zinc powder are used to replace the tin powder and indium powder used in the operation, respectively, and the remaining steps are the same as those in Example 1.

[0104] Performance testing

[0105] The room temperature compressive strength was determined with reference to the test method in GB / T5072-2023 "Test method for room temperature compressive strength of refractory materials". The high temperature flexural strength of 1250°C×0.5h was determined with reference to the test method in GB / T3002-2017 "Test method for high temperature flexural strength of refractory materials". The low carbon magnesia carbon bricks prepared in the embodiments and comparative examples were heat treated at 1400°C×2h, cooled naturally, and then the bulk density and apparent porosity were determined with reference to the method in GB / T2997-2015 "Test method for bulk density, apparent porosity and true porosity of dense shaped refractory products".

[0106] Table 1 Performance of low carbon magnesia carbon bricks in Examples 1-5 and Comparative Examples 1-2

[0107]

[0108] By analyzing Examples 1-5 and Comparative Examples 1-2 and combining with Table 1, it can be seen that the low-carbon magnesium carbon bricks prepared by the embodiment scheme are significantly higher than those of Comparative Example 1 in room temperature compressive strength and 1250°C×0.5h high temperature flexural strength, indicating that the waste magnesium carbon sand obtained after treatment has a better combination effect than the waste magnesium carbon sand obtained by directly mixing the original sand. Compared with Comparative Example 2, the two strength properties and volume density of the embodiment are not as good as those of Comparative Example 2. This may be because the copper powder and zinc powder used in Comparative Example 2 have higher metal hardness and bulk density, and the low-carbon magnesium carbon bricks are increased in compression strength and density properties to a certain extent after mixing.

[0109] Analyze Examples 1-5 and Comparative Examples 1-2 and combine Table 1 and Figure 1 It can be seen that the low-carbon magnesium carbon bricks prepared by the embodiment scheme have significantly lower apparent porosity than those of comparative examples 1-2. It can be inferred that the liquefied tin-indium binary alloy liquid inside the low-carbon magnesium carbon bricks after heat treatment fills part of the voids in the low-carbon magnesium carbon bricks, making the apparent porosity of the prepared low-carbon magnesium carbon bricks at a lower level.

[0110] Analyze Examples 1-5 and Comparative Examples 1-2 and combine Table 1 and Figure 1 It can be concluded that the low-carbon magnesia carbon bricks prepared by the operating method of the embodiment meet the actual production needs and are conducive to large-scale industrial production.

[0111] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A low carbon magnesia carbon brick, characterized in that: The invention is prepared from the following raw materials in parts by weight: 65-75 parts of fused magnesia sand, 20-24 parts of waste magnesia carbon sand, 3-5 parts of graphite, and 5-7 parts of phenolic resin adhesive; The waste magnesia carbon sand is prepared by the following steps: (1) crushing, wet-grinding and sieving the used magnesia carbon bricks, and screening according to the particle size to obtain raw sand A, raw sand B and raw sand C; the particle size of the raw sand A is 2-2.5 mm, the particle size of the raw sand B is 0.5-1 mm, and the particle size of the raw sand C is ≤0.05 mm; (2) mixing raw sand A with a silica-based sol liquid to obtain a mixed mortar, and then drying and crushing the mixed mortar to obtain magnesium carbon sand of a first particle size; (3) mixing tin powder, indium powder and raw sand B, wet grinding to obtain a mixed slurry, adding a binder, stirring, drying under anaerobic conditions, and crushing to obtain mixed sand particles, and screening the mixed sand particles with a particle size in the range of 1-2 mm as the second particle size magnesium carbon sand; (4) heating the raw sand C and subjecting it to oxygen treatment, and cooling it to obtain magnesium carbon sand of the third particle size; (5) Mix the first-size magnesia carbon sand, the second-size magnesia carbon sand and the third-size magnesia carbon sand; The silicon-based sol solution is prepared from water, tetraethyl orthosilicate, γ-glycidyloxypropyltrimethoxysilane, hydrochloric acid, polyvinyl pyrrolidone, and N,N,N-trimethyl chitosan; In the step (4), the temperature-raising and oxygen-passing treatment includes a first stage of temperature-raising, oxygen-passing, and a second stage of temperature-raising.

2. A low carbon magnesia carbon brick according to claim 1, characterized in that: In the step (2), the silicon-based sol solution is prepared from water, tetraethyl orthosilicate, γ-glycidyloxypropyltrimethoxysilane, 0.1 mol / L hydrochloric acid, polyvinyl pyrrolidone, and N,N,N-trimethyl chitosan in a mass volume ratio of (30-35) g: (3-3.5) g: 1 g: (1-2.5) mL: 0.15 g: (0.2-0.3) g.

3. A low carbon magnesia carbon brick according to claim 1, characterized in that: In the step (2), the particle size of the first-size magnesia carbon sand is 2.5-3 mm.

4. A low carbon magnesia carbon brick according to claim 1, characterized in that: In the step (3), the mass ratio of tin powder, indium powder and raw sand B is (5-7): (1-1.5): (50-75).

5. The low carbon magnesia carbon brick according to claim 1, characterized in that: In step (4), the temperature-raising and oxygen-passing treatment includes a first stage of temperature-raising, oxygen-passing, and a second stage of temperature-raising, and the operation is as follows: Stage 1 heating: heating to 500-600℃ at a rate of 5-7℃ / min; Oxygen flow: oxygen was introduced at a rate of 20 mL / min, and then stopped after 10 min; Second stage heating: heating to 745-825℃ at a rate of 10-15℃ / min.

6. A low carbon magnesia carbon brick according to claim 1, characterized in that: In the step (5), the first-size magnesia-carbon sand, the second-size magnesia-carbon sand and the third-size magnesia-carbon sand are mixed in a mass ratio of 1:2:

1.

7. A method for preparing a low-carbon magnesium-carbon brick as claimed in claim 1, characterized in that: The steps include: The fused magnesia sand, waste magnesia carbon sand, graphite and phenolic resin binder are stirred and mixed, and then transferred to a mold for pressure pressing and forming, and heat treated with a drying gun, and then baked to obtain low-carbon magnesia carbon bricks.

8. The method for preparing a low-carbon magnesia-carbon brick according to claim 7, characterized in that: The pressurized compression molding is performed at a pressure of 135-175 MPa.

9. The method for preparing a low-carbon magnesium-carbon brick according to claim 7, characterized in that: The temperature of the heat treatment with the drying gun is 550-650° C., and the treatment time is 3-5 seconds.

10. The method for preparing a low-carbon magnesia-carbon brick according to claim 7, characterized in that: The baking is carried out at 150-250° C. for 12-15 hours.

Citation Information

Patent Citations

  • Aluminum-magnesium-carbon brick and preparation method thereof

    CN117658605B

  • High-adhesiveness city cast copper sculpture coating containing benzotriazole and preparing method thereof

    CN105860727A

  • Magnesia carbon brick for converter and preparation method of brick

    CN108083819A